Legal Certainty of Electronic Certificates in Relation to Discrepancies Between Previous and Current Land Conditions - Putra, Rudi Adi Setya (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The background to this problem is that Land Registration is a series of activities carried out by the government continuously, sustainably and regularly and the maintenance of physical and legal data is regulated in Article 1 number 9 of Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units and Land Registration. Modernization has encouraged the government to implement a gradual digital transformation that will replace analog certificates with electronic ones with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities. The formulation of the problem in this study is What are the Legal Consequences of Analog Certificates Becoming Electronic Certificates? And How is Legal Certainty Regarding Land Conditions in Previous Measurement Letters Different from Current Physical Land Conditions? The theory used is the Land Registration theory of A.P. Parlindungan and the theory of legal certainty according to Gustav Radbruch. The method used in this study with the type of normative juridical research, namely library legal research or secondary data with primary, secondary and tertiary legal material sources. The research approach used is the statutory, conceptual, case and analytical approach and the technique of collecting legal materials is carried out by identifying and inventorying positive legal regulations, book literature, journals and other legal material sources. The legal material analysis technique is carried out with systematic and grammatical interpretation. The conclusion of the research results shows that the Legal Consequences of Analog Certificates to Electronic Certificates are not much different in the Regulation of the Minister of Agrarian Affairs and Spatial Planning of the National Land Agency Number 3 of 2023 in the registration of Electronic Certificate activities carried out through a media transfer program. Legal Certainty regarding the condition of the land in the Previous Measurement Letter is Different from the Current Physical Condition of the Land that the Certificate is a strong proof of rights regarding the physical data of the measurement letter and the legal data of the land book but not absolute, then Article 22 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning of the National Land Agency Number 3 of 2023, land registration and maintenance of land data must run in parallel and data must be updated for each change so that legal certainty of land rights is valid and in accordance with the latest conditions.